Reincarnation in Plato and Yoruba traditional belief (2012)
Science claims that humans do not know what happens after death. Most people, if not all, are curious to know what, if anything, happens after death. In the history of ideas, many theories have been set forth about the issue of immortality and afterlife. Immortality of the soul is a prevalent idea in many religions. Both Western and African religious and philosophical ideas are not devoid of this doctrine. The Greek philosopher - Plato presents, perhaps, the purest example of the concepts of immortality of the soul and reincarnation. The word "reincarnation" is derived from Latin and it literally means entering the flesh again. Metempsychosis is the Greek equivalent word that corresponds roughly in meaning with reincarnation which also connotes life after death, as either human or animal, thereby, emphasizing the continuity of the soul, not the flesh. The doctrine of immortality of the soul is one of the most important subjects in metaphysics. Plato, like the Yoruba, believes that there is a state of existence that goes beyond the limit of this present mortal life span and this can be attained by human through some forms of immortality such as reincarnation. That there can be some kind of continuation in existence after death is attested to by the actions, beliefs, and practices of the living people such as veneration of the dead, concept of the living dead and belief in divine reward and punishment. Plato in the Phaedo, Republic and Timaeus asserts that the soul is a pre-existent and immaterial entity which is released front the body at the time of death and can rejoin the body or another body after reincarnation. The Yoruba traditional belief, as espoused by Makinde, Abimbola and Dopamu, also share the belief that at death, the soul, being a spiritual entity, departs from the body at death and returns to Olódumarè for reincarnation. The process of reincarnation in Plato and Yoruba. traditional thought involves a change from the old form to a new one, and at times from human to non-human. As presented in Plato and Yoruba traditional belief matching the old and the new form of the soul is problematic because there is no means of identifying them. Although there is no empirical proof of ultimate survival after the death of the body, this paper explores the generally held belief among the Yoruba of Nigeria and Platonic philosophy that the soul can reincarnate in another form after the death of one body or the other. It also examines the problem of self - identity generated by the concept of reincarnation